2022
DOI: 10.3389/fpsyg.2021.815180
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Satisfaction, Compassion Fatigue and Hardiness Among Nurses: A Comparison Before and During the COVID-19 Outbreak

Abstract: BackgroundNurses provide the majority of health-care services and face numerous health challenges during an epidemic. During the COVID-19 epidemic, nurses are subjected to physical, mental, and social disorders that impair their quality of life and hardiness. Therefore, it is important to be aware of the situation of nurses. The current study aimed to compare the compassion satisfaction, compassion fatigue and hardiness among nurses before and during the COVID-19 outbreak.Materials and MethodsThis cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 47 publications
0
16
1
Order By: Relevance
“…ProQOL domains assessed in nurses during similar time frames found moderate levels of CS and CF and no significant difference in mean scores was found between survey periods. In comparison to the current study, this group of nurses reported lower levels of CS and higher levels of CF 54. Elevated rates of BO during early stages of the pandemic have been reported by hospital-based PTs, however, no baseline assessment exists for comparison 55.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…ProQOL domains assessed in nurses during similar time frames found moderate levels of CS and CF and no significant difference in mean scores was found between survey periods. In comparison to the current study, this group of nurses reported lower levels of CS and higher levels of CF 54. Elevated rates of BO during early stages of the pandemic have been reported by hospital-based PTs, however, no baseline assessment exists for comparison 55.…”
Section: Discussioncontrasting
confidence: 81%
“…In comparison to the current study, this group of nurses reported lower levels of CS and higher levels of CF. 54 Elevated rates of BO during early stages of the pandemic have been reported by hospital-based PTs, however, no baseline assessment exists for comparison. 55 The current cohort exhibits scores like other health care professionals as assessed by the ProQOL.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that organizational support in medical settings is positively associated with job satisfaction, performance and patient satisfaction ( 37 ) being considered a protective factor against burnout and anxiety. Other studies also showed that higher levels of emotional support are associated with higher healthcare workers self-efficacy, better sleep quality and low levels of stress and anxiety ( 39 ), healthcare professionals being exposed to a higher risk of experiencing mental health problems and deterioration of the quality of their professional life ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…Medical staff work in stressful environments and often experience long or stressful working hours, which can impair the mental and emotional functioning of medical staff (Hossini Rafsanjanipoor et al, 2021;Zakeri et al, 2021a). On the other hand, crises exacerbate emotional problems (Zakeri et al, 2021d). A study by Huang et al during the COVID-19 epidemic in 2020 showed that the closer the disease was to health care providers, the greater was their anxiety and anger (Huang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%